Mapping Research Trends on Healthcare and Artificial Intelligence Relationship Using Bibliometric Network Analysis (Third Sector Social Economic Review, 2025)
Nowadays, artificial intelligence is a technological breakthrough that has taken its place in our daily lives and has caused radical changes and improvements in all sectors. This technological breakthrough has led to significant developments in the health sector, as in all sectors, and plays an important role in the production, presentation and access to health services. It facilitates access to health services by ensuring the formation of more effective applications and increasing efficiency in the entire process from the production to the presentation of health services, such as data analysis, robotics, machine learning, decision support systems, software production, service personalization, routing, and appointment creation. As a matter of fact, the relationship between health services and artificial intelligence and the trend and development of this relationship over the years have become a research topic. This study examining the relationship between health services and artificial intelligence was carried out in order to map it with the bibliometric network analysis method. Within the framework of bibliometric analysis, 508 articles in the Web of Science (WoS) database were included in the research. R studio program and Biblioshiny, an interface of this program, were used for the bibliometric analysis of the 508 articles included in the research. As a result of the analysis, the trends, qualities and developments of the studies conducted in the field of health services and artificial intelligence from past to present have been examined and are important in terms of guiding future studies.
Keywords: Healthcare Services; Artificial Intelligence; Biblometric Analysis; Network Analysis